Get ready for school ebook - Nolan, Janet (2023)
Students aren't the only ones who have to prepare for the first day of school. The custodian turns on the lights and sweeps the hallways. Is it time for school? Not yet! The cafeteria workers wash tables and stack lunch trays. Is it time for school? Not yet! Teachers unpack supplies and organize their classrooms. Is it time for school? Almost! The students are on their way, on foot, on bicycles, and in cars and buses. Welcome, everyone!